Technology for Obtaining HighQuality Castings from Resistance White Cast Iron - Saidmakhamadov Nosir; Docent Khalimjonov Tokhir; Docent Saidkhodjaeva Shokhista; Turaev Anvar (Genius Journals, 2022)
This article calculated the ingots in order to obtain quality castings and liquefied them in an induction furnace. In addition, the scheme of placement of the supply disk in the casting mold, which provides a uniform distribution of bending on the surface to be strengthened during the cooling of castings, is based on the level of thermal conductivity of the mold walls. It is also designed to increase the hardness and ductility of the 280X29NL alloy based on the degree of dependence of the chromium element on its dispersion during liquefaction. This serves to ensure a uniform distribution of the elements in the alloy.
Keywords: Casting; white cast iron; ferrochrome; ferromanganese